Need Analysis for Development of a Cube and Beam Volume Assessment Instrument in Macromedia Flash Based Elementary Mathematics Learning - Aziz, Khatmirul; Lestari, Wahyu; kustiono, Kustiono (Journal of Research and Educational Research Evaluation, 2019)
The background of this study was that teacher has difficulty in overseeing the evaluation net, so that the potential for collaboration among students in evaluating was discovered, and the instruments used by teachers were still using classical assessment instruments. The purpose of this study was to determine the form of assessment instruments used by teachers in conducting evaluations, and to find out whether teachers need a Macromedia Flash-based research instrument handbook in evaluating learning. The sample used in the study was saturated or non-probability sampling where the sample was taken from SDN Bangetayu Wetan 02 class 5, the method used was quantitative and qualitative techniques, quantitative was used to calculate needs analysis and qualitative was used to collect data from samples, Data collection techniques used were using tests and non-tests where tests used cognitive assessment sheets and non-tests using data triangulation through collecting data, observations, interviews and documentation studies, the tools used were observation sheets, interview sheets, and documentation studies. The results obtained from the analysis of the needs of the cube and beam volume assessment instruments in learning Macromedia Flash based elementary school mathematics through the calculation of validity obtained Mean Square 0.956 and declared valid, as well as through the reliability test ebel obtained 0.414 so that it was declared reliable, so the needs analysis was declared valid and reliablethe development of cube and beam volume instruments in Macromedia Flash-based elementary mathematics learning is urgently needed. Manfat for the community is the community will better understand how important the use of Macromedia Flash application technology in the world of education, while for science to help overcome problems in the field of assessment.